The quest of Ewilan. Book one, From one world to another - Lylian, 1975- (Euro Comics, 2018)
A teen girl named Camille is living with her adopted family in a small French town when she and her friend accidentally enter the world of Gwendalavir where she discovers that her real name is "Ewilan" and her real parents sent her to this world to save her from the war in Gwendalavir. Ewilan learns the situation is critical in her home world and she, along with her new companions, must face her destiny as the one who was chosen to save Gwendalavir from its enemies--the evil lizard-like Ts'lichs who block one's imagination to eliminate resistance and use a human species named the Rais to carry out brutal attacks.